Traitement intra-artériel des métastases hépatiques de cancer colorectal - Pellerin, O. (J Radiol, 2011)
Colorectal carcinoma is a major public health concern with its yearly mondial incidence of about one million cases and yearly mortality of 500,000 cases. The liver is the organ most frequently affected by metastases with a frequency of 40 to 60% (contemporaneous in 25% of cases). While surgical resection is the only curative therapy, many patients are not such candidates due to the infiltrative nature of the liver metastases. Systemic chemotherapy and biotherapy regimens are the conventional treatment options for patients with multiple liver metastases. Under such circumstances, intra-arterial therapy may play a major role. We will review the main types of endovascular therapies for liver metastases from colorectal carcinoma including indications, results and potential complications.